2021
DOI: 10.22543/0733.141.1343
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Establishing a Green Climate: Face-To-Face Interaction between Leaders and Employees in the Microsystem

Abstract: This study explores the processes of establishing a green organizational climate in small-scale companies. Previous studies have primarily focused on factors associated with pro-environmental behaviour in large organizations. The role of a green organizational climate—specifically, the interactional processes involved in the construction of a green climate—has largely been unexplored. Entrepreneurial small companies constitute an ideal arena in which to study the initial phase of greening processes. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
5
0
1
Order By: Relevance
“…Ecocentric philosophy produced a conceptual framework for ecocentric management in a North American study, which includes ecological sensing, values, envisioning, and implementation in organizations (Hernández & Muñoz, 2021). Non‐Western countries can use an EL view to help develop human‐nature linkages and promote green standards by talking to people face‐to‐face, displaying environmental practices, and setting up training programs (Curran, 2021; Flagstad et al, 2021; Mukherjee et al, 2020). The present study also observed research in cross‐country empirical perspective on the possibility of an ecocentric worldview to promote common values, self‐transcending purpose, and personal insight (Gardner & Paulin, 2018; Manolopoulos, 2021; Sheridan et al, 2019; Zegers, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Ecocentric philosophy produced a conceptual framework for ecocentric management in a North American study, which includes ecological sensing, values, envisioning, and implementation in organizations (Hernández & Muñoz, 2021). Non‐Western countries can use an EL view to help develop human‐nature linkages and promote green standards by talking to people face‐to‐face, displaying environmental practices, and setting up training programs (Curran, 2021; Flagstad et al, 2021; Mukherjee et al, 2020). The present study also observed research in cross‐country empirical perspective on the possibility of an ecocentric worldview to promote common values, self‐transcending purpose, and personal insight (Gardner & Paulin, 2018; Manolopoulos, 2021; Sheridan et al, 2019; Zegers, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The interactions between leaders and subordinates may occur frequently and in the long term. However, the employees' experience of support (as a resource given by a leader) encourages their green behavior the most and strengthens the green organizational climate (Flagstad et al, 2021). Mouro and Duarte (2021) found that employees who felt that their companies value and support the workers' sustainable behavior (perceived high commitment of their organization to sustainability, a feature of a green organizational climate) exhibited more sustainable behavior.…”
Section: Green Organizational Climate As a Mediator Between Sustainab...mentioning
confidence: 99%
“…The interactions between leaders and subordinates may occur frequently and in the long term. However, the employees' experience of support (as a resource given by a leader) encourages their green behavior the most and strengthens the green organizational climate (Flagstad et al. , 2021).…”
Section: Literature Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Etablering av klima-og naturregnskap er en måte å gjøre egen virksomhet grønnere på. Innen organisasjonspsykologi har norske forskere undersøkt hvordan små bedrifter jobber for å bli grønnere, og et saerlig interessant funn er at det «grønne innholdet» i daglige interaksjoner kan vaere like viktig som en overordnet miljøstrategi (Flagstad et al, 2021).…”
Section: Psykologers Bidrag Til Atferdsendringunclassified